Las caminatas aleatorias no son de este mundo. Teoría y revisión bibliográﬁca sobre evidencia empírica. (2005)
The empirical evidence gathered in this survey related to the hypothesis that stock returns follow a random walk, led us to the conclusion that random walks are not from this world. Besides the fact that the study was performed in a developed or an emerging market, the conclusion is the same. The random walk hypothesis is rejected since the series of stock returns covered by these studies do not follow an identical, independent distribution, and these exhibit some level of autocorrelation. The difference between developed and emerging markets is rather due to the magnitude of the serial dependence which prevents agents from obtaining excess returns in the ﬁrst type of markets.